A framework of good governance in regulating religious extremism in Malaysia - Akhmetova, Elmira; Aminudin, Rabi'ah; Ahmad, Nadzrah; Sy Shiekh, Syahirah Sharifah; Jaafar, Muhammad Izzuddin (IIUM Press, 2021)
This paper presents a framework for regulating religious extremism based on principles of good governance. The first part provides a general study into the definitions of extremism and religious extremism. It asserts that religious sentiment can be utilised by terrorist organisations and radical movements to mobilise the masses. The paper further suggests that religious extremism is becoming a severe concern in Malaysia, which was for decades hailed as an oasis of moderate Islam. The second part of the paper analyses the factors contributing to the rise of religious extremism in Malaysia using a quali-quantitative method that incorporates survey data gathered in KL in 2019 by the authors, expert interviews, and secondary literature. It identifies two levels of factors, individual and socio-cultural/governance, that contribute to the spread of extremist understanding of religion. It suggests that human behaviour has become more receptive to violence and that the individual and collective understanding of religion has become more radical today due to personal grievances, social environment and global realities. Thus, the process of reducing extremism and radicalism in the Muslim world should encompass the individual, societal and transnational stratum. Extremism and radicalisation of societies are the manifestation of the absence of good governance. Thus, the last part of the paper highlights that adhering to good governance assists authorities in regulating societies’ immoderate behaviour by providing wellbeing, safety and happiness to the overwhelming majority of the population. It proposes a framework that can provide a moderate and authentic understanding of Islamic principles and serve as an instrument in creating an amicable and harmonious social and political environment in Malaysia. This framework can improve national security by promoting the basic principles of good governance such as transparency, participation, equality, justice, moderation and accountability, which are ingrained in the spirit of Islam.